Spektofotometri Derivatif dan Aplikasinya dalam Bidang Farmasi - Liliek Nurhidayati (JURNAL ILMU KEFARMASIAN INDONESIA, 2007)
Derivative spectrophotometry is a method for the simultaneous determination of drugs mixtures due to their overlapping spectra. Since the practical introduction of the concept of spectral data derivatization, the derivative spectrophotometry technique was applied. This review describes the theoretical and instrumental aspects of derivative spectrophotometry and some of its applications in pharmaceutical analysis since 1999.